Peningkatan Kapabilitas Kader Kesehatan dan Ibu Baduta dalam Upaya Penanggulangan Stunting Melalui "Bumbu Banten" di Kabupaten Pandeglang - Siti Novy Romlah; Rita Dwi Pratiwi; Astuti; Diah Permata Sari (Pelita Masyarakat, 2023)
Community Service (PkM) in this study aims to enhance the capabilities of Health Cadres and Mother-Child Duos in addressing the issue of stunting through the utilization of Bumbu Banten in the village of Pasireurih. The background lies in the limited knowledge among the community regarding Complementary Feeding (MPASI) and the prevalence of instant MPASI provision. The majority of Pasireurih village residents are engaged in the agriculture sector, showing potential in utilizing local resources for MPASI production. The objectives of PkM include improving the community's knowledge, skills, and motivation in providing adequate MPASI, utilizing local food resources, and recognizing the ease of MPASI preparation. PkM also aims to enhance the nutritional status of toddlers and empower health cadres and mothers in Pasireurih. The PkM methodology involves lectures, discussions, and practical training. Results demonstrate goal attainment, mastery of planned materials, and positive evaluations of MPASI preparation practices by toddler's mothers. This PkM has successfully increased awareness and the capabilities of the Pasireurih community in addressing stunting issues through the utilization of local resources and locally-informed MPASI.